(6+2x)(3+3x)=8

Simple and best practice solution for (6+2x)(3+3x)=8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6+2x)(3+3x)=8 equation:


Simplifying
(6 + 2x)(3 + 3x) = 8

Multiply (6 + 2x) * (3 + 3x)
(6(3 + 3x) + 2x * (3 + 3x)) = 8
((3 * 6 + 3x * 6) + 2x * (3 + 3x)) = 8
((18 + 18x) + 2x * (3 + 3x)) = 8
(18 + 18x + (3 * 2x + 3x * 2x)) = 8
(18 + 18x + (6x + 6x2)) = 8

Combine like terms: 18x + 6x = 24x
(18 + 24x + 6x2) = 8

Solving
18 + 24x + 6x2 = 8

Solving for variable 'x'.

Reorder the terms:
18 + -8 + 24x + 6x2 = 8 + -8

Combine like terms: 18 + -8 = 10
10 + 24x + 6x2 = 8 + -8

Combine like terms: 8 + -8 = 0
10 + 24x + 6x2 = 0

Factor out the Greatest Common Factor (GCF), '2'.
2(5 + 12x + 3x2) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(5 + 12x + 3x2)' equal to zero and attempt to solve: Simplifying 5 + 12x + 3x2 = 0 Solving 5 + 12x + 3x2 = 0 Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by '3'. 1.666666667 + 4x + x2 = 0 Move the constant term to the right: Add '-1.666666667' to each side of the equation. 1.666666667 + 4x + -1.666666667 + x2 = 0 + -1.666666667 Reorder the terms: 1.666666667 + -1.666666667 + 4x + x2 = 0 + -1.666666667 Combine like terms: 1.666666667 + -1.666666667 = 0.000000000 0.000000000 + 4x + x2 = 0 + -1.666666667 4x + x2 = 0 + -1.666666667 Combine like terms: 0 + -1.666666667 = -1.666666667 4x + x2 = -1.666666667 The x term is 4x. Take half its coefficient (2). Square it (4) and add it to both sides. Add '4' to each side of the equation. 4x + 4 + x2 = -1.666666667 + 4 Reorder the terms: 4 + 4x + x2 = -1.666666667 + 4 Combine like terms: -1.666666667 + 4 = 2.333333333 4 + 4x + x2 = 2.333333333 Factor a perfect square on the left side: (x + 2)(x + 2) = 2.333333333 Calculate the square root of the right side: 1.527525232 Break this problem into two subproblems by setting (x + 2) equal to 1.527525232 and -1.527525232.

Subproblem 1

x + 2 = 1.527525232 Simplifying x + 2 = 1.527525232 Reorder the terms: 2 + x = 1.527525232 Solving 2 + x = 1.527525232 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 1.527525232 + -2 Combine like terms: 2 + -2 = 0 0 + x = 1.527525232 + -2 x = 1.527525232 + -2 Combine like terms: 1.527525232 + -2 = -0.472474768 x = -0.472474768 Simplifying x = -0.472474768

Subproblem 2

x + 2 = -1.527525232 Simplifying x + 2 = -1.527525232 Reorder the terms: 2 + x = -1.527525232 Solving 2 + x = -1.527525232 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = -1.527525232 + -2 Combine like terms: 2 + -2 = 0 0 + x = -1.527525232 + -2 x = -1.527525232 + -2 Combine like terms: -1.527525232 + -2 = -3.527525232 x = -3.527525232 Simplifying x = -3.527525232

Solution

The solution to the problem is based on the solutions from the subproblems. x = {-0.472474768, -3.527525232}

Solution

x = {-0.472474768, -3.527525232}

See similar equations:

| 111118n^2+60n+50=0 | | 2(3k-1)/5+4=3k(5) | | a+10=67 | | (2x^2+7x)-(x^2-6x-2)= | | 5x^2+20x+31=0 | | p+50=149 | | 2x-56=14 | | 10p(3s)= | | 9(3n-4)=(7n+4)1 | | 25y^2-144=0 | | 22=-4p-10 | | 10p(3s+10p)= | | n-14=92 | | 4+6p-6p=p-2 | | m+20=30 | | x^2+6x+5=9 | | 3y+19=47+2y | | 3/7H=-18 | | 5(6x+2)+6=30x+16 | | 5y=12y+20 | | 2+7(10+15k)= | | .8x-2.9=.3 | | -x^2=-4x | | 3x-5x=8x | | x-(8-3x)=2(3x+5) | | 3m^2+30m+75= | | 8-(2n-6)=2-3n | | -8y^2=10y | | 4n+7=13 | | 8s-15=-64+s | | 5(2k+9)=105 | | -6x+4=-3x^2 |

Equations solver categories